Kritik Metodologis dan Substansial terhadap Perbandingan Hukum Kontrak Antara Hukum Islam dan Hukum Indonesia: Methodological and Substantial Criticism of the Comparison of Contract Law Between Islamic Law and Indonesian Law - Imron Rosadi; Sofyan Al-Hakim (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study critically examines Atharyanshah Pueri's article on the comparison of Islamic contract law and Indonesian law, against the background of the importance of high methodological standards in the study of comparative law, especially in the context of Indonesian legal pluralism. The approach of this study uses normative legal techniques and critical analysis, with a comparative methodology evaluation framework based on contemporary comparative legal theory. Meta-analysis techniques were used to assess the methodological framework, quality of argumentation, and engagement with primary sources and relevant literature. The study found that Puneri's article has significant methodological weaknesses, such as the absence of a clear comparative framework, limitations in the use of primary sources, lack of contextualization, and superficial substance analysis of both Islamic contract law and Indonesian law. The article also fails to identify the comparative tertiums that are essential for comparative studies. These weaknesses demonstrate the urgency of developing a more rigorous comparative legal research methodology, including the application of functional theoretical frameworks, the integration of case studies, and contextual analysis that includes socio-economic dynamics. This constructive academic criticism is expected to spur the improvement of the quality of legal research in Indonesia with international academic standards.